Feasibility study for detection of retinal amyloid in clinical trials: The Anti‐Amyloid Treatment in Asymptomatic Alzheimer's Disease (A4) trial. Issue 1 (17th August 2021) - Ngolab, Jennifer; Donohue, Michael; Belsha, Alison; Salazar, Jennifer; Cohen, Paula; Jaiswal, Sandhya; Tan, Veasna; Gessert, Devon; Korouri, Shaina; Aggarwal, Neelum T.; Alber, Jessica; Johnson, Ken; et al.
Abstract: Introduction: The retina and brain exhibit similar pathologies in patients diagnosed with neurodegenerative diseases. The ability to access the retina through imaging techniques opens the possibility for non‐invasive evaluation of Alzheimer's disease (AD) pathology. While retinal amyloid deposits are detected in individuals clinically diagnosed with AD, studies including preclinical individuals are lacking, limiting assessment of the feasibility of retinal imaging as a biomarker for early‐stage AD risk detection. Methods: In this small cross‐sectional study we compare retinal and cerebral amyloid in clinically normal individuals who screened positive for high amyloid levels through positron emission tomography (PET) from the Anti‐Amyloid Treatment in Asymptomatic Alzheimer's Disease (A4) trial as well as a companion cohort of individuals who exhibited low levels of amyloid PET in the Longitudinal Evaluation of Amyloid Risk and Neurodegeneration (LEARN) study. We quantified the number of curcumin‐positive fluorescent retinal spots from a small subset of participants from both studies to determine retinal amyloid deposition at baseline. Results: The four participants from the A4 trial showed a greater number of retinal spots compared to the four participants from the LEARN study. We observed a positive correlation between retinal spots and brain amyloid, as measured by the standardized uptake value ratio (SUVr). Discussion: The results of this small pilot study support the use of retinal fundus imaging for detecting amyloid deposition that is correlated with brain amyloid PET SUVr. A larger sample size will be necessary to fully ascertain the relationship between amyloid PET and retinal amyloid both cross‐sectionally and longitudinally.